Effect of sampling duration on culturable and viable bioaerosol determination when using Rutgers Electrostatic Passive Sampler (REPS). (November 2022) - Grogan, Sydonia N.C.M.; Mainelis, Gediminas
Abstract: Rutgers Electrostatic Passive Sampler (REPS) is a passive bioaerosol sampler composed of a permanently polarized polyvinylidene fluoride (PVDF) film wound into a 3D printed film holder. In order to investigate the effect of sampling duration on its performance, REPS was deployed in an indoor and outdoor location in Spring and Fall over continuing sampling periods ranging from 24 h to 21 days. Reference concentrations were determined by an active, culture-based sampler twice daily. REPS samples were analyzed for culturable bacteria and fungi as well as adenosine triphosphate (ATP) activity. The number of culture forming units (CFU) determined by REPS exhibited strong and positive correlations with sampling duration for culturable bacteria (Pearson r > 0.899, p < 0.05) and fungi (r > 0.902, p < 0.05) for both test locations. Similar results were observed for ATP activity in outdoor samples (r > 0.844, p < 0.05). REPS showed an equivalent flow rate (Qeq ) as high as 4.86 ± 4.90 L/min when sampling bacteria outdoors. When sampling bacteria indoors, the Qeq was lower: 0.37 ± 0.78 L/min. When sampling fungi, the Qeq outdoors was also higher than that indoors. Overall, the study demonstrated that REPS is able to effectively capture airborne culturable bacteria and fungi by passive means of collection in indoor and outdoor environments while maintaining bioaerosol culturability for over 21 days of continuous sampling. Further studies will explore methods to improve the sample detection limit by using different sample concentration techniques as well as the sampler's integration with the next-generation sequencing techniques. Highlights: The impact of sampling duration on bioaerosol culturability was investigated. REPS, a passive bioaerosol sampler, sampled continuously from 1 to 21 days. Equivalent sampling flowrates of REPS are similar to those of some active samplers. REPS maintains sample culturability and viability during 21 days of sampling.